HISTOPATHOLOGICAL AND BIOCHEMICAL INVESTIGATION OF THE PATIENTS WHO HAD LIVER STEATOZIS BY ULTRASONOGRAPHY - Ali Reşit BEYLER; Nihat SİPAHİ and Ömer DÖNDERİCİ and; ÖZDEN and; ti ÖRMECİ and Abdülkadir DÖKMECİ and Negüz SÜMER and Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-